2017
DOI: 10.7717/peerj.3414
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphic markers of genes FTO, KCNJ11, CDKAL1, SLC30A8, and CDKN2B with type 2 diabetes mellitus in the Russian population

Abstract: BackgroundThe association of type 2 diabetes mellitus (T2DM) with the KCNJ11, CDKAL1, SLC30A8, CDKN2B, and FTO genes in the Russian population has not been well studied. In this study, we analysed the population frequencies of polymorphic markers of these genes.MethodsThe study included 862 patients with T2DM and 443 control subjects of Russian origin. All subjects were genotyped for 10 single nucleotide polymorphisms (SNPs) of the genes using real-time PCR (TaqMan assays). HOMA-IR and HOMA-β were used to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 62 publications
2
26
0
Order By: Relevance
“…In 2016, Kommoju, U. J. et al reported that the rs7754840C allele was associated with T2DM in Indian population [25]. In 2017, Nikitin, A. G. et al identi ed the association of rs10946398C with T2DM in Russian population [26]. In the current study, the rs4712524G, rs10946398C and rs7754840C allele and genotype were also con rmed to be associated with T2DM.…”
Section: Discussionsupporting
confidence: 62%
“…In 2016, Kommoju, U. J. et al reported that the rs7754840C allele was associated with T2DM in Indian population [25]. In 2017, Nikitin, A. G. et al identi ed the association of rs10946398C with T2DM in Russian population [26]. In the current study, the rs4712524G, rs10946398C and rs7754840C allele and genotype were also con rmed to be associated with T2DM.…”
Section: Discussionsupporting
confidence: 62%
“…Besides, genetic predisposition, sedentary lifestyle, and excessive calorie intake may also contribute to T2DM [4]. Studies have shown that the incidence of diabetes is related to genetic factors and is the result of the joint action of multiple gene loci [4,5]. Genome-wide association studies (GWAS), genome-wide linkage analysis and candidate-gene approaches are wildly applied in studying the genetic basis of T2DM [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS), genome-wide linkage analysis and candidate-gene approaches are wildly applied in studying the genetic basis of T2DM [1,3]. To date, multiple genes have been functionally implicated in the pathogenesis of T2DM [1,4]. However, the susceptibility of T2DM varies across populations due to differences in interracial gene polymorphisms and haplotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) for T2D have been widely carried out in different racial types, with the exception of T2D-associated genes, obesity-associated and birth weight-associated genes have also been found to relate to T2D, but results were inconsistent. For example, loci rs13266634 in gene SLC30A8 was associated with T2D in Russian and the Danish populations [10,11], while the link disappeared in African populations [12]. A common obesity-associated gene, FTO, has been confirmed to have an association with T2D in different countries, and several gene loci were associated with insulin resistance such as rs9939609 and rs1558902 [13,14].…”
Section: Introductionmentioning
confidence: 99%